Die Vermittlung von Informationskompetenz in der Ärztlichen Zentralbibliothek des Universitätsklinikums Hamburg-Eppendorf - Kintzel, Melanie; Sunderbrink, Norbert (GMS Medizin – Bibliothek – Information, 2014)
[english] This article introduces the range of information literacy classes at the Medical Library of the University Medical Center Hamburg-Eppendorf. It focuses on current advancement of the training courses, especially on the curricular information literacy class which is part of the elective module “academic research” in the new degree programme “iMED Hamburg”.